2020
DOI: 10.3390/diagnostics10040188
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Circulating microRNAs in Prostate Cancer Reveals Diagnostic Biomarker Potential

Abstract: Early detection of prostate cancer (PC) is paramount as localized disease is generally curable, while metastatic PC is generally incurable. There is a need for improved, minimally invasive biomarkers as current diagnostic tools are inaccurate, leading to extensive overtreatment while still missing some clinically significant cancers. Consequently, we profiled the expression levels of 92 selected microRNAs by RT-qPCR in plasma samples from 753 patients, representing multiple stages of PC and non-cancer controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
(52 reference statements)
1
23
0
Order By: Relevance
“…Another diagnostic miRNA panel was recently proposed by Fredsøe and colleagues [ 164 ]. The study profiled plasma samples ( n = 753) of patients affected by PCa in different stages, including BPH, localized and advanced disease, as well as control subjects.…”
Section: The Diagnostic and Prognostic Power Of Mirnas In Prostatementioning
confidence: 99%
“…Another diagnostic miRNA panel was recently proposed by Fredsøe and colleagues [ 164 ]. The study profiled plasma samples ( n = 753) of patients affected by PCa in different stages, including BPH, localized and advanced disease, as well as control subjects.…”
Section: The Diagnostic and Prognostic Power Of Mirnas In Prostatementioning
confidence: 99%
“…Correlated expression levels of miR-20a, miR-21, miR-145, and miR-221 [ 186 ], miR-17, miR-20a, miR-20b, miR-106a [ 187 ] as well as miR-16, miR-148a and miR-195 [ 188 ] in the plasma could significantly distinguish high risk patients from those with low risk and some of these miRNAs were shown to confer an aggressive phenotype upon overexpression in vitro as well as an accelerated biochemical recurrence [ 187 ]. Fredsoe et al validated a blood-based miRNA diagnostic model comprising of 4 miRNAs (miR-375, miR-33a-5p, miR-16-5p and miR-409-3p), called bCaP, in 753 patients with benign prostate lesions and multiple stages of prostate cancer and showed that combined with PSA, digital rectal examination and age bCaP predicted the outcomes of biopsies better than PSA alone [ 189 ].…”
Section: Blood-based Liquid Biopsy Marker Candidatesmentioning
confidence: 99%
“…Their levels can be modified in all stages of PCa, from incipient tumors to metastatic states. These molecules look promising but further studies for validations are needed [ 79 , 80 ].…”
Section: Other Perspectivesmentioning
confidence: 99%